2010
DOI: 10.1016/j.febslet.2010.01.047
|View full text |Cite
|
Sign up to set email alerts
|

CBFA2T3–ZNF651, like CBFA2T3–ZNF652, functions as a transcriptional corepressor complex

Abstract: a b s t r a c tA significant proportion of the human genome codes for transcription factors. Balanced activity of transcriptional activators and repressors is essential for normal development and differentiation. Previously we reported that a classical C 2 H 2 zinc finger DNA binding protein ZNF652 functionally interacts with CBFA2T3 to repress transcription of genes containing ZNF652 consensus DNA binding sequence within the promoters of these target genes. Here we show that ZNF651 is a ZNF652 paralogue that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 11 publications
0
12
1
Order By: Relevance
“…In breast cancer cell lines ZBTB10 is suppressed by ROS-microRNA27a thereby enhancing ERα alpha expression and mediating estrogen effects [17]. The ZNF652 (17q21.32) locus codes for a DNA binding protein thought to act as a tumor suppressor gene in breast cancer [69], [70], [71] that is also co-expressed with the androgen receptor in prostate cancer [72]. TDGF3 , teratocarcinoma derived growth factor 3, is the only significant region identified on the X chromosome ((Xq22.3).…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer cell lines ZBTB10 is suppressed by ROS-microRNA27a thereby enhancing ERα alpha expression and mediating estrogen effects [17]. The ZNF652 (17q21.32) locus codes for a DNA binding protein thought to act as a tumor suppressor gene in breast cancer [69], [70], [71] that is also co-expressed with the androgen receptor in prostate cancer [72]. TDGF3 , teratocarcinoma derived growth factor 3, is the only significant region identified on the X chromosome ((Xq22.3).…”
Section: Discussionmentioning
confidence: 99%
“…By targeting FOXO3 genes, miR‐155 increases cancer cell viability, and proliferation and by targeting RAS homolog family member A (RhoA) it triggers EMT, metastasis and even BC drug resistance, although the precise mechanism of this requires more research . The downregulation of ZNF652, a potential target of miR‐155, can increase the invasion, and metastasis of BC . Several studies have observed miR‐155‐stimulated cell proliferation, invasion, EMT, and repressed apoptosis through inhibition of the expression of TP53INP1 in BC cells .…”
Section: Introductionmentioning
confidence: 99%
“…3 The downregulation of ZNF652, a potential target of miR-155, can increase the invasion, and metastasis of BC. 54,55 Several studies have observed miR-155-stimulated cell proliferation, invasion, EMT, and repressed apoptosis through inhibition of the expression of TP53INP1 in BC cells. 51,[56][57][58] Moreover, miR-21 and miR-155 have the same effect on common targets in apoptosis pathways such as APAF-1, BID, CASP2, CASP3, CASP6, CASP9, CASP10.…”
Section: Introductionmentioning
confidence: 99%
“…Location 16q24.3 Protein Member of the "ETO" family. Functions as a transcriptional repressor via interaction with corepressor complexes; do not directly bind DNA, but interacts with transcription factors such as BCL6, PLZF, GFI1, ZNF651 and ZNF652 (Kumar et al, 2010).…”
Section: Cbfa2t3mentioning
confidence: 99%